Patients with obesity-related comorbidities have higher disability compared with those without obesity-related comorbidities: results from a cross-sectional study. Issue 1 (March 2016) - Sirtori, Anna; Brunani, Amelia; Capodaglio, Paolo; Berselli, Maria E.; Villa, Valentina; Ceriani, Francesca; Corti, Stefania; Leonardi, Matilde; Raggi, Alberto
Abstract : The aim of the present study was to describe disability in adult obese patients with obesity-related comorbidities, and to compare it with that of patients without obesity-related comorbidities. Two groups of obese patients were administered a set of 166 International Classification of Functioning, Disability and Health (ICF) categories; on the basis of this set, count-based indexes were developed for each ICF component and difference between patients with and without comorbidities were assessed with independent-sample t -test and Cohen's d as a measure of effect size. ICF categories in which at least 20% of patients reported a problem were considered relevant for describing functioning of obese patients; for each of them, the risk of having obesity-related comorbidities was calculated using odds ratio and 95% confidence interval. A total of 106 inpatients were enrolled in the study: 68 ICF categories reached the 20% threshold, and 31 of them were relevant only among patients with comorbidities. The presence of obesity-related comorbidities was associated with an increased risk of bodily impairments and limitations in performing daily activities. Compared with patients without obesity-related comorbidities, those with comorbidities showed higher disability. Comorbidities contribute to obesity-related disability, and our results support the importance of early rehabilitation interventions to reduce disability.